2021
DOI: 10.3389/fonc.2020.586401
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Prognosis of Secondary Bladder Cancer After Radiation Therapy for Rectal Cancer: A Large Population-Based Cohort Study

Abstract: BackgroundAlthough radiation therapy (RT) improves local control for rectal cancer (RC), the long-term risks from RT, including development of a secondary malignancy, are controversial. The risk and prognosis of secondary bladder cancer (SBC) in RC patients undergoing RT have not been adequately studied. Our goal is to investigate the impact of RT on the risk of developing SBC and assess their survival outcomes.MethodsThis large population-based study included RC patients as their initial primary cancer from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Indeed, a recent study using data from the SEER database found that patients with breast cancer not exposed to chemotherapy or radiotherapy were at higher risk for incident CV disease compared with the general population, especially without tumor resection. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study using data from the SEER database found that patients with breast cancer not exposed to chemotherapy or radiotherapy were at higher risk for incident CV disease compared with the general population, especially without tumor resection. 30 …”
Section: Discussionmentioning
confidence: 99%
“…During RT, high doses of ionizing radiation are delivered, which is a form of high-energy electromagnetic radiation reaching deeper internal body structures and eventually causing apoptosis ( 8 , 9 ). However, RT increases the risk of developing radiation-induced complications in normal tissues and may promote progressive changes in the extracellular matrix and the development of a vascular reaction, which could increase the risk of secondary tumors in the irradiated field ( 4 , 10 , 11 ). The bladder is usually within the field of irradiation in the pelvis and is exposed to more radiation than organs in the non-pelvic area ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it can reduce the local relapse rate of patients, evident survival benefits were not achieved in terms of longterm efficacy [3,4]. In addition, due to the high damage of radiotherapy to LARC patients, anal function, urination function, and sexual function worsen with time, which dramatically reduces the patient's life quality and increases the risk for secondary tumors such as bladder cancer [5][6][7]. With the continuous development of TME-related techniques in clinical practice, both the R0 resection rate and anus preservation rate are becoming more and more ideal.…”
Section: Introductionmentioning
confidence: 99%